2021
DOI: 10.1038/s41416-021-01587-4
|View full text |Cite
|
Sign up to set email alerts
|

Diverse ‘just-right’ levels of chromosomal instability and their clinical implications in neoadjuvant treated gastric cancer

Abstract: Background The Cancer Genome Atlas (TCGA) consortium described EBV positivity(+), high microsatellite instability (MSI-H), genomic stability (GS) and chromosomal instability (CIN) as molecular subtypes in gastric carcinomas (GC). We investigated the predictive and prognostic value of these subtypes with emphasis on CIN in the context of neoadjuvant chemotherapy (CTx) in GC. Methods TCGA subgroups were determined for 612 resected adenocarcinomas of the stom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…These results are consistent with the literature suggesting a more favourable prognosis for EBV-positive or MSI gastric cancer 3 , 6–8 . In agreement with the present data, some previous studies 4 , 6 , 9 suggested that patients with CIN cancer have the poorest prognosis. However, there are also studies suggesting that CS cancers have the poorest prognosis 3 , 7 and others 2 , 10 showing no difference in survival between TCGA subtypes.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results are consistent with the literature suggesting a more favourable prognosis for EBV-positive or MSI gastric cancer 3 , 6–8 . In agreement with the present data, some previous studies 4 , 6 , 9 suggested that patients with CIN cancer have the poorest prognosis. However, there are also studies suggesting that CS cancers have the poorest prognosis 3 , 7 and others 2 , 10 showing no difference in survival between TCGA subtypes.…”
Section: Discussionsupporting
confidence: 93%
“…However, the relationship between CIN or GS subtype and patient prognosis is less clear. Some studies 4 , 6 , 9 have suggested that patients with CIN gastric cancer have the poorest prognosis. Others have concluded that the GS subtype is related to poor prognosis 3 , 7 , or that there is no relationship between survival and GS or CIN subtype 2 , 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [ 25 ] found that gastric cancer patients with CIN were prone to HER2-positive and mucinous adenocarcinoma. Kohlruss et al [ 26 ] investigated the use of CIN in neoadjuvant chemotherapy for gastric cancer. In conclusion, CIN offers a new direction for targeted therapy of malignant tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Some groups have referred to CIN as aneuploidy or polyploidy, while others have defined CIN as multiple structural rearrangements or frequent changes in the chromosome number (Tsai et al, 2018). The formation of CIN is caused by the breakdown of the DNA replication fork induced by an oncogene, which leads to DSB and genomic instability (Kohlruss et al, 2021). Although CIN in cancer has been studied extensively, its exact cause remains unclear.…”
Section: Dna Damage Repair In Gastric Cancer Because Of Helicobacter ...mentioning
confidence: 99%